2016
DOI: 10.3390/brainsci6040043
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Ethanol Exposure and Whisker Clipping Disrupt Ultrasonic Vocalizations and Play Behavior in Adolescent Rats

Abstract: Prenatal ethanol exposure can result in social deficits in humans and animals, including altered social interaction and poor communication. Rats exposed to ethanol prenatally show reduced play fighting, and a combination of prenatal ethanol exposure and neonatal whisker clipping further reduces play fighting compared with ethanol exposure alone. In this study, we explored whether expression of hedonic ultrasonic vocalizations (USVs) correlated with the number of playful attacks by ethanol-exposed rats, rats su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…22 kHz vocalizations occur in a variety of stressful situations, including social isolation [81], exposure to predators [82], and withdrawal from drugs [83]. Conversely, 50 kHz USVs tend to occur in more rewarding situations, such as mating, juvenile play, drug administration, and “tickling” [80, 84, 85]. We measured characteristics of USVs during social interaction to gain insight into affective states.…”
Section: Discussionmentioning
confidence: 99%
“…22 kHz vocalizations occur in a variety of stressful situations, including social isolation [81], exposure to predators [82], and withdrawal from drugs [83]. Conversely, 50 kHz USVs tend to occur in more rewarding situations, such as mating, juvenile play, drug administration, and “tickling” [80, 84, 85]. We measured characteristics of USVs during social interaction to gain insight into affective states.…”
Section: Discussionmentioning
confidence: 99%
“…P28 P42 LE 10 min At P28, during play female control whisker clipped rats produced more 22 kHz USVs than other female groups. At P42, during play male rats overall had more 50 kHz USVs than female rats [98]. At P1, both male and female pups with prenatal cocaine exposure (PCE) produced fewer distress USVs than saline or untreated pups and male pups with PCE produced fewer USVs with at least one observable harmonic than male saline or untreated pups.…”
Section: Pup Distress Usvsmentioning
confidence: 99%
“…There is also a significant number of studies assessing the long-term effects of various early life stressors on 50-kHz USV emission during rough-and-tumble play. Such studies focused, for instance, on the effects of prenatal exposure to ethanol [80,81] and valproic acid [82,83]. Recent studies found that prenatal ethanol exposure leads to an enhanced emission of 22-kHz USV at the expense of 50-kHz USV during rough-and-tumble play in males but not females [84].…”
Section: Rough-and-tumble Play and Ultrasonic Vocalizations In Ratsmentioning
confidence: 99%